PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER BERDASARKAN METODEWHOLE BRAIN TEACHING DENGAN BERBANTUAN MANGA STUDIO PADA SUB POKOK BAHASAN KUBUS DAN BALOK KELAS VIII SMP - Syafitri, Ratna; Dafik, D; Hobri, H (Kadikma, 2014)
Abstract: This researchwas aimedto describe the process of the development of a characterbased Mathematics Learning Material basedon Whole Brain Teaching methodwith Manga Studio for cubes and cuboid topics at eight gradejunior high school. The learning developmental model refers to four D models proposed by Thiagarajan. The products of this research are lesson plan, student book, worksheet, and evaluation test.The resultsshow that the coeficient of validaty for each product are lesson plan reachs 0,94, student book reachs 0,91, work sheet reachs 0,91, and evaluation test reachs 0,82. it can be concluded that the characterbased Mathematics Learning Material basedon Whole Brain Teaching methodwith Manga Studio have fulfilledthe validity, practice, and effective criteria. Key words:Character,Whole Brain Teaching, Manga Studio,Four D models